Civil Liability for Accidents at Sea - Gahlen, Sarah Fiona (Springer, 2016)
​This book presents a study on civil liability for accidents at sea, with a focus on the interests of parties that are not contractually participating in the maritime enterprise. Shipping and the maritime offshore industry are among the most international businesses in the world, and the operation of ships and facilities at sea can involve very different interests in a wide variety of relationships.